Electronic wedge brakes: a review of design, modeling, control strategies, and testing methodologies - Soomro, Mehrullah; Hassan, Mohd Khair; Mustafa Abro, Ghulam E.; Marimuthu, Maran (Institute of Electrical and Electronics Engineers Inc., 2025)
This review examines Electronic Wedge Brake (EWB) technology, a revolutionary vehicle braking system that uses a self-reinforcing wedge mechanism to increase braking force. We demonstrate the transformative potential of this system to improve performance, efficiency, and integration with advanced vehicle safety technologies by charting the transition from hydraulic and electro-mechanical brakes (EMBs) to EWBs. This review analyses state-of-the-art EWB design, modelling, and control contributions from 2002 to 2024. Our research shows that this sector has received little attention despite its importance in vehicular technology. We carefully study EWBs, focussing on the brake factor and how wedge geometry, actuation methods, and material selections affect braking. The examination addresses reverse braking, backlash, wear, Caliper rigidity, and mathematical modelling methods such as state-space representations, system identification, and lead screw, motor, and wedge dynamics. We also examine prototype development and validation methods such real-world vehicle testing, hardware-in-the-loop (HIL) simulations, and dynamometer testing to resolve the experimental-simulation mismatch. EWB control techniques such conventional PID, advanced sliding mode control, ADRC, fuzzy logic, and LQR are prioritised to maintain system stability around the optimal operating point. This evaluation synthesises EWB design, modelling, testing, and control and identifies important problems and future research areas to promote mainstream use, unlike earlier evaluations. The forward-thinking perspective of this study underlines the possibility for hybrid/electric vehicles to seamlessly combine EWB with Anti-lock Braking System (ABS), electronic speed control (ESC), and regenerative braking systems. This integration will enable next-generation intelligent braking solutions. This evaluation emphasises Electronic Wedge Brake technology’s contribution to safer, more efficient, and sustainable transportation and UN Sustainable Development Goals including affordable and clean energy for sustainable cities and communities.